Filsafat Ilmu dan Ilmu Pendidikan - Melisa Marlinton Marlinton; Herlina Herlina Herlina; Suraidah Suraidah Suraidah; Yenny Puspita Puspita; Darwin Efendi Efendi (Syntax Idea, 2022)
Philosophy is the study of the nature of things, such as humans, nature, and God. Philosophy is seen as a humanizing process so that humans are able to develop and actualize themselves with all the original potential that exists within themselves. Education develops from curiosity, curiosity, and the desire to seek reality which is a characteristic of humans. Education is a special human effort to express reality, in order to enable humans to socialize with each other, build dialogue by acknowledging other people, and increase their human dignity. Philosophy is an inseparable part of educational practice, but the existence of this philosophy seems to have begun to be abandoned. Considering that philosophy is an inseparable part of education, this paper attempts to reaffirm the relationship between philosophy and education. The method used to determine the relationship between philosophy and the author's education is to study literature. Based on the results of the study of literature clearly shows the relationship between philosophy and educational practice as in curriculum formulation and educational theories.